Ex 10.3

Ex 10.3, 1

Ex 10.3, 2

Ex 10.3, 3 Important

Ex 10.3, 4

Ex 10.3, 5 Important You are here

Ex 10.3, 6

Ex 10.3, 7

Ex 10.3, 8

Ex 10.3, 9 Important

Ex 10.3, 10 Important

Ex 10.3, 11

Ex 10.3, 12 Important

Ex 10.3, 13 Important

Ex 10.3, 14

Ex 10.3, 15 Important

Ex 10.3, 16 Important

Ex 10.3, 17

Ex 10.3, 18 (MCQ) Important

Last updated at April 21, 2021 by Teachoo

Hello! Teachoo has made this answer with days (even weeks!) worth of effort and love. Since your board exams are coming, why not help Teachoo create more videos and content by supporting us? Please click on this link to make a donation

Hello! Teachoo has made this answer with days (even weeks!) worth of effort and love. Since your board exams are coming, why not help Teachoo create more videos and content by supporting us? Please click on this link to make a donation

Ex 10.3, 5 Show that each of the given three vectors is a unit vector: 1/7 (2𝑖 ̂ + 3𝑗 ̂ + 6𝑘 ̂), 1/7 (3𝑖 ̂ – 6𝑗 ̂ + 2𝑘 ̂), 1/7 (6𝑖 ̂ + 2𝑗 ̂ – 3𝑘 ̂), Also, show that they are mutually perpendicular to each other. 𝑎 ⃗ = 1/7 (2𝑖 ̂ + 3𝑗 ̂ + 6𝑘 ̂) = 2/7 𝑖 ̂ + 3/7 𝑗 ̂ + 6/7 𝑘 ̂ 𝑏 ⃗ = 1/7 (3𝑖 ̂ − 6𝑗 ̂ + 2𝑘 ̂) = 3/7 𝑖 ̂ – 6/7 𝑗 ̂ + 2𝑘/7 𝑘 ̂ 𝑐 ⃗ = 1/7 (6𝑖 ̂ + 2𝑗 ̂ - 3𝑘 ̂) = 6/7 𝑖 ̂ + 2/7 𝑗 ̂ – 3/7 𝑘 ̂ Magnitude of 𝑎 ⃗ = √((2/7)^2+(3/7)^2+(6/7)^2 ) |𝑎 ⃗ | = √(4/49+9/49+36/49) = √(49/49) = 1 Since |𝑎 ⃗ | = 1 So, 𝑎 ⃗ is a unit vector. Magnitude of 𝑏 ⃗ = √((3/7)^2+((−6)/7)^2+(2/7)^2 ) |𝑏 ⃗ | = √(9/49+36/49+4/49)= √(49/49) = 1 Since |𝑏 ⃗ | = 1 So, 𝑏 ⃗ is a unit vector. Magnitude of 𝑐 ⃗ = √((6/7)^2+(2/7)^2+((−3)/7)^2 ) |𝑐 ⃗ | = √(36/49+4/49+9/49) = √(49/49) = 1 Since |𝑐 ⃗ | = 1, So, 𝑐 ⃗ is a unit vector Now, we need to show that they are mutually perpendicular to each other. So, 𝒂 ⃗. 𝒃 ⃗ = 𝒃 ⃗. 𝒄 ⃗ = 𝒄 ⃗ . 𝒂 ⃗ = 0 Thus, they are mutually perpendiculars to each other. 𝑎 ⃗ = 2/7 𝑖 ̂ + 3/7 𝑗 ̂ + 6/7 𝑘 ̂ 𝑏 ⃗ = 3/7 𝑖 ̂ – 6/7 𝑗 ̂ + 2/7 𝑘 ̂ 𝒂 ⃗. 𝒃 ⃗ = 2/7 . 3/7 + 3/7 (−6/7) + 6/7 . 2/7 = 6/49 − 18/49 + 12/49 = 0 𝑏 ⃗ = 3/7 𝑖 ̂ − 6/7 𝑗 ̂ + 2/7 𝑘 ̂ 𝑐 ⃗ = 6/7 𝑖 ̂ + 2/7 𝑗 ̂ – 3/7 𝑘 ̂ 𝒃 ⃗. 𝒄 ⃗ = 3/7 . 6/7 + (−6/7) 2/7 + 2/7 . ((−3)/7) = 18/49 − 12/49 − 6/49 = 0 𝑐 ⃗ = 6/7 𝑖 ̂ + 2/7 𝑗 ̂ − 3/7 𝑘 ̂ 𝑎 ⃗ = 2/7 𝑖 ̂ + 3/7 𝑗 ̂ + 6/7 𝑘 ̂ 𝒄 ⃗. 𝒂 ⃗ = 6/7 . 2/7 + 2/7. 3/7 + ((−3)/7) 6/7 = 12/49 + 6/49 − 18/49 = 0